Start technique - Recent findings - Sanders, R.; Bonnar, S. (coachesinfo.com)
Based on the findings of recent research, the following conclusions and implications can be drawn: 1 Performance in the start is strongly related to overall swim performance. 2 It is unclear whether particular postures on the blocks such as those used for grab, track, and handle starts and their variants yield an advantage compared to the others. 3 There are indications that, regardless of the posture used, intensive practice of dive starts results in significant improvement even among experienced competitive swimmers. 4 There is evidence to suggest that the underwater phase following entry is highly important. Therefore, much more research should be focused on this phase. 5 There is some evidence that anthropometric factors have a strong influence on performance. In particular, taller and heavier swimmers may have an advantage. More research is required to establish how anthropometric characteristics affect performance. 6 A major implication of the existing research is that coaches and swimmers should devote considerable effort to minimising resistance and maximising propulsion during the underwater phase of starts. The timing of initiating kicking actions is an important consideration in 'fine tuning' the underwater phase of starts.